Ultrastructural and Molecular Analysis of Ribose-Induced Glycated Reconstructed Human Skin - Rigon, Roberta Balansin [UNESP]; Kaessmeyer, Sabine; Wolff, Christopher; Hausmann, Christian; Zhang, Nan; Sochorova, Michaela; Kovacik, Andrej; Haag, Rainer; Vavrova, Katerina; Ulrich, Martina; Schaefer-Korting, Monika; Zoschke, Christian (Mdpi, 2018)
Aging depicts one of the major challenges in pharmacology owing to its complexity and heterogeneity. Thereby, advanced glycated end-products modify extracellular matrix proteins, but the consequences on the skin barrier function remain heavily understudied. Herein, we utilized transmission electron microscopy for the ultrastructural analysis of ribose-induced glycated reconstructed human skin (RHS). Molecular and functional insights substantiated the ultrastructural characterization and proved the relevance of glycated RHS beyond skin aging. In particular, electron microscopy mapped the accumulation and altered spatial orientation of fibrils and filaments in the dermal compartment of glycated RHS. Moreover, the epidermal basement membrane appeared thicker in glycated than in non-glycated RHS, but electron microscopy identified longitudinal clusters of the finest collagen fibrils instead of real thickening. The stratum granulosum contained more cell layers, the morphology of keratohyalin granules decidedly differed, and the stratum corneum lipid order increased in ribose-induced glycated RHS, while the skin barrier function was almost not affected. In conclusion, dermal advanced glycated end-products markedly changed the epidermal morphology, underlining the importance of matrix-cell interactions. The phenotype of ribose-induced glycated RHS emulated aged skin in the dermis, while the two to three times increased thickness of the stratum granulosum resembled poorer cornification.
Keywords: advanced glycated end products; aging; diabetes; electron microscopy; nanomedicine; ribose; reconstructed human skin; skin absorption